Pengaruh pendapatan, kepercayaan dan religiusitas terhadap minat untuk membayar zakat penghasilan - Sumadi, Sumadi; Priliastuti, Dini (Journal of Economics Research and Policy Studies, 2021)
This study aims to determine the effect of income, belief, and religiosity on the interest in paying zakat income (study of residents of Makamhaji Kartasura). This study uses a quantitative approach to the population of Makamhaji Kartasura Village residents. The sampling technique uses probability sampling to analyze the data using a multiple linear regression model. The results showed that income had no significant effect on the interest in paying zakat income. In contrast, trust and religiosity have a significant effect on the interest in paying zakat income. Meanwhile, simultaneous income, belief, and religiosity have influenced the residents of Makamhaji Kartasura Village to pay zakat income. This research model contributes to explaining the role of trust and religiosity on increasing zakat income.